Single-Stream Recycling Inspires Selective Fish Passage Solutions for the Connectivity Conundrum in Aquatic Ecosystems. (16th September 2020) - Zielinski, Daniel P; McLaughlin, Robert L; Pratt, Thomas C; Goodwin, R Andrew; Muir, Andrew M
Abstract: Barrier removal is a recognized solution for reversing river fragmentation, but restoring connectivity can have consequences for both desirable and undesirable species, resulting in a connectivity conundrum. Selectively passing desirable taxa while restricting the dispersal of undesirable taxa (selective connectivity) would solve many aspects of the connectivity conundrum. Selective connectivity is a technical challenge of sorting an assortment of things. Multiattribute sorting systems exist in other fields, although none have yet been devised for freely moving organisms within a river. We describe an approach to selective fish passage that integrates ecology and biology with engineering designs modeled after material recycling processes that mirror the stages of fish passage: approach, entry, passage, and fate. A key feature of this concept is the integration of multiple sorting processes each targeting a specific attribute. Leveraging concepts from other sectors to improve river ecosystem function may yield fast, reliable solutions to the connectivity conundrum.